Kebijakan Optimalisasi Anggaran Melalui Revisi Anggaran dalam Upaya Meningkatkan Capaian Kinerja di UIN Alauddin Makassar - Gustang, A. (JURNAL ILMIAH GEMA PERENCANA, 2024)
This policy paper discusses budget optimization policies through effective and efficient budget revisions to improve the performance achievements of planners at UIN Alauddin Makassar. The budget revision policy is an important tool to ensure the budget is used efficiently, effectively, and accountably. At UIN Alauddin Makassar, there are several obstacles in implementing the budget revision policy, such as low budget absorption, decreased performance achievements, lack of clarity in the budget revision mechanism, slow budget revision process, and lack of stakeholder involvement. This study uses qualitative methods with descriptive data analysis techniques. Data was obtained from document studies and field observations. The study results show inefficiencies in the budget allocation process, budget absorption is still low, and the work culture does not support efficient and effective use of the budget. This study resulted in recommendations that UIN Alauddin Makassar needs to take several steps, such as: preparing clear and comprehensive budget revision guidelines, building a monitoring and evaluation system for the budget revision process, increasing HR capacity in handling the budget revision process, increasing stakeholder involvement in the budget revision process, analyzing the impact of budget revisions on performance achievements before carrying out revisions, increasing synergy between budget revision policies and other policies, and utilizing information technology. By implementing these steps, it is hoped that UIN Alauddin Makassar can increase the optimization of budget absorption, increase the efficiency and effectiveness of budget use, increase performance achievements, increase stakeholder satisfaction, and increase public trust.